(untitled) (Research, Society and Development, 2022)
Brazil is among the largest dairy cattle producers in the world. In confined systems, the disposal of waste from the production process needs specific locations that respect environmental legislation, and, when deposited incorrectly, generate environmental impacts. Due to its composition, the waste generated can be used through stabilization processes, for the production of organic fertilizer and for the generation of energy as sustainable alternatives. The present work aimed to identify the environmental impacts in the energy production chain by biogas. A case study was carried out based on a dairy cattle breeding facility that uses its residues to produce biogas and organic fertilizer. Based on the information and using a bibliographic review, it was possible to make notes on the possible impacts generated in the production of sustainable energy, such as atmospheric pollution from the burning of biogas. It was concluded that, although they can have environmental impacts, the use of biodigesters for waste treatment and biogas generation reduces the polluting potential that the waste has.